허리통증 환자의 한국판 일상동작 공포설문지의 신뢰도와 타당도 - 차용준(Yong-Jun Cha); 김경(Kyoung Kim) (한국콘텐츠학회 논문지, 11(5), 2011)
The purpose of this study was to test the reliability and validity of the Korean version of the fear of daily activities questionnaire (FDAQ) for low back pain patients. Seventy-three subjects with low back pain were participated in this study. The subjects completed ten standardized self-administered questionnaires that measure fear of specific daily activities. The reliability of the acquired data was determined by the intra-class correlation coefficient (ICC) and the Cronbach's ${α}$ for internal consistency. Constructive validity was analyzed by factor analysis, and concurrent validity was acquired from comparison FDAQ scores to the visual analogue scale (VAS) and Oswestry disability index (ODI) scores. The test-retest reliability of the Korean version of the FDAQ showed good ICC (2,1)= 0.96 (95%CI 0.94.0.98) and Cronbach's alpha value was 0.93. Factor analysis suggested two factors solution consisting of spinal loading and spinal movement/posture, it explained 76.1% of the total variance. The concurrent validity was moderately related with pain and disability. Therefore, the Korean version of the FDAQ is a useful method for measuring the fear of daily activities of patients with low back pain. 본 연구는 허리통증 환자를 대상으로 한국판 일상동작 공포설문지에 대한 신뢰도와 타당도를 검증하기 위하여 실시하였다. 허리 통증이 있는 총 73명의 환자를 대상으로 하였고, 각 대상자는 10가지의 일상동작들에 대한 두려움 정도를 자기-기입식으로 설문지를 작성하였다. 평가-재평가에 신뢰도를 알아보기 위하여 급간내상관계수를 구하였고, 각 문항에 대한 내적일치도는 Cronbach's ${α}$값을 이용하였다. 구성타당도를 알아보기 위하여 요인분석을 실시하였고, 시각 상사척도(VAS)와 Oswestry 장애지수(ODI)와의 피어슨 상관관계 계수를 구하여 공인타당도를 분석하였다. 한국판 일상동작 공포설문지의 평가-재평가간 급간내상관계수(ICC)는 0.96(95%CI 0.94~0.98)으로 높은 신뢰도를 보였고, Cronbach's ${α}$값은 0.93으로 내적일치도가 높게 나타났다. 요인분석 결과 척추부하, 척추운동/자세유지로 총 2요인으로 분리되었고, 총 분산은 76.1%였다. 통증과 기능장애와 관련된 공인타당도는 양호한 양의 상관관계를 나타내었다. 따라서 한국판 일상동작 공포설문지는 허리통증 환자들의 일상동작 시 발생할 수 있는 두려움을 평가하는데 유용하게 쓰일 수 있을 것으로 본다.